2020
DOI: 10.1371/journal.pone.0237694
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of performance of two SARS-CoV-2 Rapid IgM-IgG combined antibody tests on capillary whole blood samples from the fingertip

Abstract: Background The SARS-CoV-2 (Severe Acute Respiratory Syndrome CoronaVirus 2) is responsible for the infectious respiratory disease called COVID-19 (COronaVIrus Disease 2019). In response to the growing COVID-19 pandemic, point-of-care (POC) tests have been developed to detect specific antibodies, IgG and IgM, to SARS-CoV-2 virus in human whole blood. We conducted a prospective observational study to evaluate the performance of two POC tests, COVID-PRESTO ® and COVID-DUO … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 16 publications
0
47
0
1
Order By: Relevance
“…Performances of this test have already been assessed in real life, regardless of the manufacturer’s instructions. The sensitivity of COVID-PRESTO® test ranged from 10% for patients having experienced their first symptoms from 0 to 5 days earlier to 100% in patients whose symptoms occurred more than 15 days earlier 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Performances of this test have already been assessed in real life, regardless of the manufacturer’s instructions. The sensitivity of COVID-PRESTO® test ranged from 10% for patients having experienced their first symptoms from 0 to 5 days earlier to 100% in patients whose symptoms occurred more than 15 days earlier 5 .…”
Section: Methodsmentioning
confidence: 99%
“…The blood sample is then collected with a capillary micropipette and deposited in the appropriate well of the test cassette. COVID-PRESTO ® ’s performance has been evaluated in a recent clinical study, and the test showed a specificity of 100% and a sensitivity ranging from 10% (when the test was done 0–5 days after symptoms onset) to 100% (when performed ≥15 days after experiencing the first symptoms) [ 11 ]. Those results were obtained in a controlled setting where the test was performed by trained professionals.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential that the performance of newly developed POCT assays be thoroughly evaluated before use. Performance between different POCT assays varies greatly (see Supplementary Table 4 ) [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] ] with a range of different assay sensitivities. The meta-analysis by ML Bastos in July 2020 [ 3 ] showed that POCT assays up till April 2020 had varied sensitivities (36.4%–100%).…”
Section: Discussionmentioning
confidence: 99%